2023
DOI: 10.3390/ani13152538
|View full text |Cite
|
Sign up to set email alerts
|

Mastitis in Dairy Cattle: On-Farm Diagnostics and Future Perspectives

Chiara Tommasoni,
Enrico Fiore,
Anastasia Lisuzzo
et al.

Abstract: Mastitis is one of the most important diseases in dairy cattle farms, and it can affect the health status of the udder and the quantity and quality of milk yielded. The correct management of mastitis is based both on preventive and treatment action. With the increasing concern for antimicrobial resistance, it is strongly recommended to treat only the mammary quarters presenting intramammary infection. For this reason, a timely and accurate diagnosis is fundamental. The possibility to detect and characterize ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 91 publications
0
8
0
Order By: Relevance
“…Mastitis stands out as the most widespread and economically impactful disease in dairy cattle globally, primarily attributed to diminished milk production, discarded milk, premature culling, and associated treatment expenses [92]. Bovine mastitis is a polymicrobial disease with the principal etiological agents being Staphylococcus aureus, Streptococcus dysgalactiae, and Streptococcus uberis [93].…”
Section: Mastitismentioning
confidence: 99%
“…Mastitis stands out as the most widespread and economically impactful disease in dairy cattle globally, primarily attributed to diminished milk production, discarded milk, premature culling, and associated treatment expenses [92]. Bovine mastitis is a polymicrobial disease with the principal etiological agents being Staphylococcus aureus, Streptococcus dysgalactiae, and Streptococcus uberis [93].…”
Section: Mastitismentioning
confidence: 99%
“…It is important to note that not all intramammary infections (IMIs) need Pathogens 2024, 13, 423 2 of 15 antibiotic treatment. The decision to administer antibiotics should be based on diagnostic and sensitivity test outcomes, rather than on presumptive treatment [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Bexiga et al showed that microbiological methods allow the identification of only 47% of mastitis cases compared to the PCR method [15]. Moreover, traditional methods, such as the Somatic Cell Count (SCC), offer quick, cost-effective and field-friendly solutions, but they do not provide specific detection [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although antibiotic administration remains the primary treatment for mastitis, the specific antibiotic class required to exterminate the pathogens that cause mastitis can vary [ 27 ]. Moreover, the Ministry of Agriculture, Forestry, and Fisheries of Japan, advocates a reduction in antibiotic administration to treat bovine mastitis in accordance with Roberson’s recommendations [ 24 ].…”
mentioning
confidence: 99%
“…The traditional method of bacterial cultivation, commonly employed in a microbiological laboratory or on farms, is widely used for pathogen identification [ 4 , 27 ]. However, bacterial culture requires more than 24 hr to proliferate; such a long cultivation period often worsens the symptoms of mastitis.…”
mentioning
confidence: 99%